2010
DOI: 10.2174/1874213001003030001
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Fear: Ecological Implications of Being Afraid~!2009-09-09~!2009-11-16~!2010-02-02~!

Abstract: "Predation risk" and "fear" are concepts well established in animal behavior literature. We expand these concepts to develop the model of the "landscape of fear". The landscape of fear represents relative levels of predation risk as peaks and valleys that reflect the level of fear of predation a prey experiences in different parts of its area of use. We provide observations in support of this model regarding changes in predation risk with respect to habitat types, and terrain characteristics. We postulate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
568
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(586 citation statements)
references
References 54 publications
11
568
0
7
Order By: Relevance
“…Finally, the hedgehogs tracked in this study were found further from badger activity than a randomly generated set of tracking fixes. These results support the notion that predator avoidance is one possible cause of hedgehogs' selection of rural villages (Micol et al 1994;Laundre et al 2010;Hof et al 2012). However, badger presence was not the only cause of the site differences in home range size, there were differences between the two sites with badgers and the two sites without, plausibly due to other differences between the sites such as resource availability.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, the hedgehogs tracked in this study were found further from badger activity than a randomly generated set of tracking fixes. These results support the notion that predator avoidance is one possible cause of hedgehogs' selection of rural villages (Micol et al 1994;Laundre et al 2010;Hof et al 2012). However, badger presence was not the only cause of the site differences in home range size, there were differences between the two sites with badgers and the two sites without, plausibly due to other differences between the sites such as resource availability.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, in the most recent study, the difference in functional responses between the invasive Hemimysis anomala and native Mysis salemaai was exacerbated by the presence of a higher trophic-level predator (Barrios-O'Neill et al in press). Derivation of functional responses thus require attention to the myriad effects of threats to the individual, the so-called 'landscape of fear' (see Laundré et al 2010) or 'ecology of fear' (see Clinchy et al 2013). Finally, whilst not essential in the overall goal of comparing functional responses of invaders and natives towards prey, disentangling the relative roles of predator 'novelty' and prey 'naievete' (see Sih et al 2010) would provide insight into reasons for the higher functional responses of invaders and hence insight into ecological impact.…”
Section: Challenges Future Research and Applicationsmentioning
confidence: 99%
“…Animals will forage in safe areas if they can (Banks 2001;Verdolin 2006) but when they must forage in risky areas, they adopt many behaviours to manage their risk, including reduced time allocation, increased vigilance, central place foraging and group foraging (Lima and Dill 1990). Thus predation risk has clearly demonstrated sublethal behavioural impacts on prey, including herbivores, modifying where they go and how long they stay at a feeding patch (Brown et al 1999;Laundre et al 2010).…”
Section: Dealing With Predation Riskmentioning
confidence: 99%